A Two-Stage DEA Model to Evaluate the Performance of Iberian Banks - Moutinho, Victor (2022)
This paper’s goal is twofold: it aims to assess the performance of 58 Iberian banks and explore the relationship between such performance and the banks’ Intellectual Capital (IC) efficiency during a post-crisis period. As long as the authors are aware, there is a gap in the literature in exploring the relationship between banks’ global performance and IC efficiency. First, the Data Envelopment Analysis model was adopted to measure the efficiency of Iberian banks and rank them according to their performance. Data were collected digitally, specifically by using the Bankscope database provided by Bureau van Dijk. Results show that by improving their resources management practices, banks can significantly increase their efficiency. Then, fractional regressions were used to infer the relationship between IC’s efficiency and the scores obtained in the first stage. Results suggest that Iberian banks’ global performance is mainly determined by their human capital efficiency. Finally, this study stresses the importance of IC measurement to support more efficient decision-making by bank managers.